1981
DOI: 10.1038/292201a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular considerations relevant to the mechanism of active transport

Abstract: A small group of closely related proteins is responsible for all active transport in animal cells, and inorganic cations are the only substances transported by these enzymes. They share a common kinetic mechanism in which two fundamental conformations participate, each receiving and dispatching substrates from its unique side of the membrane. During transport, the cations must pass through their enzyme to cross the membrane and intense interest is currently focused on the possibility that the path which they f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(89 citation statements)
references
References 79 publications
5
84
0
Order By: Relevance
“…In addition to establishing the Cl-channel as a functional dimer, the results here lead to the immediate conclusion that this complex can form a "mixed-state dimer"; the M state of the channel represents a structure in which one of the protochannels is in its conducting conformation, while the other is in its nonconducting conformation. A mixed-state configuration of this type strictly breaks the protein symmetry alluded to above, but if the conformational changes involved in opening and closing are small or far removed from the subunit-subunit interface, this symmetry-breaking would not greatly destabilize the dimeric complex (11). Symmetry violations of this type are a priori forbidden in certain theories of quaternary structure of proteins, most notably the Monod-Wyman-Changeux model of cooperative allosteric interactions (14) but are permitted in others, such as Koshland's "induced-fit" theory (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to establishing the Cl-channel as a functional dimer, the results here lead to the immediate conclusion that this complex can form a "mixed-state dimer"; the M state of the channel represents a structure in which one of the protochannels is in its conducting conformation, while the other is in its nonconducting conformation. A mixed-state configuration of this type strictly breaks the protein symmetry alluded to above, but if the conformational changes involved in opening and closing are small or far removed from the subunit-subunit interface, this symmetry-breaking would not greatly destabilize the dimeric complex (11). Symmetry violations of this type are a priori forbidden in certain theories of quaternary structure of proteins, most notably the Monod-Wyman-Changeux model of cooperative allosteric interactions (14) but are permitted in others, such as Koshland's "induced-fit" theory (15).…”
Section: Discussionmentioning
confidence: 99%
“…Many membrane transport proteins have been proposed to operate as oligomers (12), and very good evidence exists for the dimeric structure of the erythrocyte Cl-exchanger (13) in particular; but the functional significance of these proposed oligomeric structures remains in doubt (11). In addition to establishing the Cl-channel as a functional dimer, the results here lead to the immediate conclusion that this complex can form a "mixed-state dimer"; the M state of the channel represents a structure in which one of the protochannels is in its conducting conformation, while the other is in its nonconducting conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, such experiments suggest that both the pump and the receptor functions are properties of the a-subunit. Quantitative binding studies reveal that the receptor site, the phosphorylation site and the ATP-binding site (Munson, 1981(Munson, , 1983Rempeters & Schoner, 1981;Ponzio et al, 1983;Bobis et al, 1983) are present in a 1:1:1 ratio on the active Na,K-ATPase molecule (Wallick et al, 1979;Robinson & Flashner, 1979;Sweadner & Goldin, 1980;Cantley, 1981;Schuurmans Stekhoven & Bonting, 1981;J0rgensen, 1982) (Stein, 1979;Repke & Dittrich, 1979) or (ii) one permanent-high-affinity ATP binding site and one permanent low-affinity, regulatory, ATP binding site per two associated a-subunits (Robinson, 1980;Fritzsch & Koepsell, 1983) or (iii) only a single a-subunit monomer containing one ATP site with changing affinity during the turnover cycle and one cardiac glycoside receptor site (Kyte, 1981;Moczydlowski & Fortes, 1981;Peters et al, 1981) is a much discussed question. These three possibilities are shown schematically in Fig.…”
Section: Receptor Topographymentioning
confidence: 99%
“…Sequence homology between the K-ATPase of Escherichia coli and the CaATPase of sarcoplasmic reticulum has been reported. On the other hand, the sequence of Ca-ATPase resembles that of the a-subunit of Na, K-ATPase (Kyte, 1981). It can be speculated that during evolution monofunctional transport systems 'fuse' to multifunctional ones.…”
Section: The Ouabain-resistance Genementioning
confidence: 99%
“…T 3 and TAG in fat cells regulate insulin secretion and insulin sensitivity by an as yet unknown mechanism (258 -266) . Additionally, T 3 regulates the expression of transmembrane enzymes K þ /Na þ and Ca 2þ ATP-ase, involved in driving membrane-bound protein pumps, which transport molecules such as glucose and amino acids into the cells (267) . Thyroid hormones reduce b-cell mass, the main source of insulin production, although several studies have demonstrated that thyroid hormones have cytotoxic effects on b-cells in vivo and in vitro.…”
Section: Interactions Between Insulin and Leptin Oestrogen Or Thyroimentioning
confidence: 99%